Microcurrent electrotherapy improves palatal wound healing: Randomized clinical trial - Miguel, Manuela Maria Viana [UNESP]; Mathias-Santamaria, Ingrid Fernandes [UNESP]; Rossato, Amanda [UNESP]; Ferraz, Laís Fernanda Ferreira [UNESP]; Figueiredo-Neto, Antônio Martins; de Marco, Andrea Carvalho [UNESP]; Casarin, Renato Corrêa Viana; Wallet, Shannon Margaret; Tatakis, Dimitris N.; Mathias, Marcio Antonio; Santamaria, Mauro Pedrine [UNESP] (My University, 2020)
Background: This study was conducted to assess the clinical, immunological, and patient-centered outcomes of microcurrent electrotherapy on palatal wound healing. Methods: This was a parallel, double-masked randomized clinical trial, in which 53 patients with ridge preservation indications were selected and randomly assigned to one of two groups. In the control (sham) group (n = 27), palatal wounds, after free gingival grafts (FGG) harvest, received sham application of electrotherapy. In the test (electrotherapy treatment [EE]) group (n = 26), palatal wounds, after FGG harvest, received application of microcurrent electrotherapy protocol. Clinical parameters, patient-centered outcomes, and inflammatory markers were evaluated, up to 90 days postoperatively. Results: The EE group achieved earlier wound closure (P <0.001) and epithelialization (P <0.05; P = 0.03) at 7 and 14 days after harvest when compared with the sham group. Painful symptomatology was reported less frequently in the EE group than in the sham group at 3-day follow-up (P = 0.008). Likewise, an improvement in Oral Health Impact Profile was reported 2 days after the procedure by the EE group (P = 0.04). In addition, favorable modulation of inflammatory wound healing markers occurred when electrotherapy was applied. Conclusion: Within the limits of the present study, it can be concluded that the use of a low-intensity electrotherapy protocol may accelerate palatal wound healing and decrease patient discomfort after FGG harvest.
Keywords: gingival recession; mucogingival surgery; wound healing / electric stimulation therapy